If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26.5 = 9.5 + 3.5(v + -4.5) Reorder the terms: -26.5 = 9.5 + 3.5(-4.5 + v) -26.5 = 9.5 + (-4.5 * 3.5 + v * 3.5) -26.5 = 9.5 + (-15.75 + 3.5v) Combine like terms: 9.5 + -15.75 = -6.25 -26.5 = -6.25 + 3.5v Solving -26.5 = -6.25 + 3.5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3.5v' to each side of the equation. -26.5 + -3.5v = -6.25 + 3.5v + -3.5v Combine like terms: 3.5v + -3.5v = 0.0 -26.5 + -3.5v = -6.25 + 0.0 -26.5 + -3.5v = -6.25 Add '26.5' to each side of the equation. -26.5 + 26.5 + -3.5v = -6.25 + 26.5 Combine like terms: -26.5 + 26.5 = 0.0 0.0 + -3.5v = -6.25 + 26.5 -3.5v = -6.25 + 26.5 Combine like terms: -6.25 + 26.5 = 20.25 -3.5v = 20.25 Divide each side by '-3.5'. v = -5.785714286 Simplifying v = -5.785714286
| P+1.4p=48 | | 2h+1=13 | | 3(x-1)+4=-2 | | 5x+3-7x=2-6+x | | 60+60*1= | | 4*x^2-69*x+24= | | -3x+10y=-19 | | 18+16x=-14 | | 5u*8g+2k*8x= | | F(x)=2x^3-9x^2+12-4 | | 3c=24+1c | | 39+4b=29 | | 2x=20+2x | | 0.6a+0.2a=0.4a+8 | | 4(3x+2)-X=-8 | | 64+11x+3=25x-3 | | 4(3x+2)-X=8 | | 3t^2-6t=-30 | | 4x-1=11x-61 | | 19-(5-7x)=-1 | | 2x^6+3x^5+8x^4+15-2+12x-8=0 | | 2X^2+6X-128=0 | | -20=-2v | | 3-3*6+2y=5 | | 2(3-x)+4x=16 | | 6x+5(x-20)=538 | | 3-3y*6+2=0 | | 3-3*6y+2=0 | | 4(3x+2)-X=1 | | y=-1-2*1 | | 3-3*6+2y=0 | | 4(3x+2)-X=11 |